Centralidade às avessas : o lugar da assistência social na proteção social brasileira - Bastos, Amanda Suelen Ferreira (2014)
The dissertation discusses the screen in social welfare policy in the contemporary scene and the centrality assumed by it in the Brazilian social protection, from the advent of SUAS, via expansion of income transfer programs, especially the Bolsa Família Program, which in the context of the crisis of capital became the main strategy to fight poverty in the country. To do so, we place the macroeconomic determinants of welfare policy and the influence of international financial organizations in shaping social policies of neo-liberal in the country, we analyze social welfare policy based on what some authors the critical field of social service call ´´assistencialização`` social policies and, finally, present their own budget mediations of focus in the current Brazilian social protection. This is an exploratory study conducted through documentary and bibliographic research, and one of their main conclusions is that through the analysis performed confirmed that social assistance is of centrality "in reverse" in the Brazilian social protection, whose character and selective focused on compensatory income transfer programs, imposes limits to consolidate this policy in the context of social law.